How Educators Can Increase and Improve Family Involvement in Mathematics Homework - Barnes, Anna (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
In order to explore the role of parental involvement in mathematics learning, this paper will begin by presenting a profile of a fifth-grade student, here called “Amber,” at an urban K-8 public elementary school in Northwest Ohio who was observed during mathematics class throughout the 2017-2018 school year. Amber’s academic performance, the role her family plays in her education, and their interactions with educators all are described below. Amber’s achievement will be defined through both in-class and homework grades. The amount and quality of assistance she receives from family members during mathematics homework is also discussed, with the goal of determining ways that family involvement in mathematics homework can be improved for this particular student. The goal is to explore the implications and conclusions which can be drawn from this example, with the aim of exploring how family involvement in mathematics homework can be increased and improved.